Impact of training and digital extension services on agricultural technology adoption and rice yields - Apsara Karki Nepal; Dyutiman Choudhary; Naba Raj Pandit; Narayan Khanal (PLoS ONE, 2025)
Although rice is the primary staple crop in Nepal, its yields have not increased sufficiently to keep pace with population growth and food security needs. The key factors contributing to this challenge is inadequate agricultural extension services that meets farmers’ demand and the low adoption rate of technologies that could enhance rice productivity. This study evaluates the effects of sequential agricultural training and real-time digital extension services on the technology adoption and rice yield in Nepal’s Western Terai, where evidence on the effectiveness of such combined intervention remains limited. Using data from a stratified random sample of 1,396 households, including treatment, control-in, and control-out groups, we assess the impact of these interventions on technology adoption and rice yield. We apply quasi-experimental methods including treatment effects model (IPWRA), seemingly unrelated regression, and instrumental variable approaches. Our findings consistently indicate that smallholder farmers who receive agricultural training combined with digital extension services have 11.4–15.7 percentage points higher adoption rate of split urea application in three doses at the recommended stages of plant growth, resulting in a 35–56% increase in rice yield compared to the reference group. These results suggest that the combined effect of agricultural training and digital extension services significantly outperforms agricultural training alone in both technology adoption and yield improvement, which is one of the key contributions of this study. The findings highlight the potential of bundled approach to enhance rice productivity and strengthen food security. However, limited Internet access in farming communities and difficulties in interpreting digital advisories may constrain the broader adoption of these agricultural practices.